ANALISIS PELUANG PENERAPAN APLIKASI SISTEM PELAPORAN KEGIATAN PEMELIHARAAN PERALATAN MEDIS BERBASIS ANDROID MELALUI PENDEKATAN TEORI SWOT DI RSUP dr WAHIDIN SUDIROHUSODO MAKASSAR - Arfan Maulana Arfan; Yahya Thamrin Yahya; Muhammad Rifai Rifai (Bina Generasi : Jurnal Kesehatan, 2022)
ABSTRACT The hospital is one of the institutions that has an important role in providing health services to the community. Availability of medical equipment that is complete and in good condition is one of the supports for the realization of improving the quality of electromedical services, especially in the supervision and maintenance of medical facilities that are more efficient and effective at Dr. Wahidin Sudirohusodo Hospital Makassar.The purpose of this study was to determine the readiness at RSUP dr Wahidin Sudirohusodo Makassar in the plan to implement an android-based medical equipment maintenance activity reporting system.This research is a qualitative research that aims to obtain a complete picture of a matter according to the view of the human being studied. This research was carried out at Dr Wahidin Sudirohusodo Hospital Makassar in July-August 2021. By involving 5 respondents who met the requirements in this study, namely the Director of Planning, Organization and General Affairs, Head of Facility Maintenance Agency, Head of Sub-Installation of Medical Equipment Maintenance, and Electromedical technical staff. Dr. Wahidin Sudirohusodo Hospital, Makassar. Data collection was done by open interview and observation. The entire interview process was recorded using audio recordings. Data is presented in narrative form.The results showed that based on the analysis with the SWOT theory approach, it was found that the chances of implementing an Android-based medical equipment maintenance reporting system application plan could be implemented well if the strengths and opportunities were combined into a good form of planning to be implemented in the process. The conclusion in this study is that dr Wahidin Sudirohusodo Hospital Makassar is ready to plan the implementation of an android-based medical equipment maintenance activity reporting system.It is hoped that all relevant parties will always try to minimize bad possibilities in the application of the android-based medical equipment maintenance activity reporting system. Keywords: Android Application, Facility Maintenance, SWOT Theory